Immunophenotypic Characterization of Childhood Acute Leukaemia in A Tertiary Care Center of Bangladesh (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Leukemia is one of the most common tumors in children. Childhood acute leukaemia (AL) is a heterogenous disease. Immunophenotyping is an essential part of the modern diagnostic workup/for typing and subtyping and prognostic stratification of AL and thus for an appropriate treatment of these complex and heterogeneous diseases.Objectives: Objective of this study was to find immunophenotypic charectarization of childhood acute leukemia in children of Bangladesh. There is very limited study done on this subject in our country. Methods: This is a retrospective observational study done in children with acute leukemia under 15 years of age, treated in two tertiary care centers for Paediatric Oncology [Combined Military Hospital Dhaka and Ahsania Mission Cancer Hospital, Mirpur, Dhaka]. Data were collected from hospital registry from 2014 to 2020 and then analyzed.Results: Total study population were 82; among them male 55%, female 45% and M:F 1:0.82. Most common age group was